Internet connectivity disruption in Lebanon (Lebanon) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Lebanon. Data sourced from IODA.
Network Disruption Incident ID: LB-2026-0268. Severity: critical. Confidence: 67%